Prevalence and Diversity of Staphylococcus aureus in Bulk Tank Milk from Community-Based Alpine Dairy Pastures in Tyrol, Austria - Nasrin Ramezanigardaloud; Igor Loncaric; Patrick Mikuni-Mester; Masoumeh Alinaghi; Monika Ehling-Schulz; Johannes Lorenz Khol; Tom Grunert (Animals)
Staphylococcus aureus frequently causes intramammary infections in dairy cows (bovine mastitis), which impair animal welfare, milk yield, and food safety. This study determined the prevalence and genetic diversity of S. aureus in bulk tank milk (BTM) samples from community-based Alpine dairy pastures in Tyrol, a major milk-producing region in Austria. Throughout the 2023 Alpine season (May–September), 60.3% (94/156) of BTM samples tested positive for S. aureus at least once over the course of up to four samplings. A total of 140 isolates collected from the 94 S. aureus-positive community-based Alpine dairy pastures revealed 33 distinct spa types, with t2953 (n = 33), t529 (n = 12), t267 (n = 11), and t024 (n = 10) being the most common. Selected isolates representing the different spa types were characterised by DNA microarray-based genotyping, multi-locus sequence typing (MLST), and antimicrobial susceptibility testing. Isolates with spa types associated with bovine-adapted CC8 (CC8bov/GTB) were identified as the most common subtype, being detected in BTM samples from 35.3% (55/156) of the pastures. This emphasises the high prevalence of this subtype in dairy herds across European Alpine countries. Other common bovine-associated subtypes were also detected, including CC97, CC151, and CC479. While antimicrobial resistance was rare, enterotoxin-producing genes were detected in all CC8bov-associated spa types. Overall, these findings underscore the importance of rigorous hygiene practices in dairy farming, particularly in community-based Alpine dairy pastures, where the risk of transmission is particularly high. It also emphasises the need for continued surveillance and subtyping to improve animal health, ensure food safety, and promote sustainable milk production.